Verification of Indirect Tensile Strength of Weathered Mudstone from H-Ometer Test Using Sigma/W Model - Ahmad, Azura (2002)
This study presents the findings determine of a comparative study to indirect tensile strength from H-Ometer test and finite element method. H-Ometer tests were carried out on weathered mudstone specimens on the axial model. Two-dimensional plane strain analysis using SIGMA/W Finite Element Method was carried out to simulate the performance of H-Ometer test on the axial model. The relationship between indirect tensile strength of the H-Ometer Test and Finite Element Method for weathered mudstones are presented. The H-Ometer results on axial model specimens showed the average indirect tensile strength is 0.102 MPa and the finite element analysis is 0.116 MPa. Consistently, results of both methods indicate that indirect tensile strength from the finite element method is slightly higher compared to the H-Ometer test. It is proposed that the relationship between indirect tensile strength from H-Ometer test and finite element method is O'FE = 1.132 O'HO where O'HO is tensile strength from H-Ometer test and O'FE is indirect tensile strength from finite element method. From the statically analysis the results show a good relationship between H-Ometer test and finite element method in indicating that the related parameters can be used to predict the indirect tensile strength of weak rock.